Scattering effects in laser attenuation system for measurement of droplet number density - Sulaiman, S.A. (Elsevier Ltd, 2014)
Laser attenuation system can be used to measure droplet number density in suspended particles including sprays, which are used in combustion studies. The system is also capable in determining the molar absorptivity of a liquid or solid medium. Nevertheless, any kind of light is known to experience scattering that is resulted from non-uniformity of the medium that the light passes through. In this paper the occurrence of light scattering in laser attenuation system for different medium is investigated. The laser attenuation system is developed and calibrated using commercial light filters of known densities. The occurrence of scattering and its significance is studied using iodine and water sprays. The study reveals that a total of about 13 of the light is scattered elsewhere. Â© 2014 Elsevier Ltd.